Interreligious Conflicts in Post-Authoritarian Indonesia: Assumptions, Causes, and Implications - Regus, Maksimus (Jurnal Politik, 2020)
While Indonesia is known as a land of religious tolerance, interreligious conflicts have been a central issue in the academe. This study attempts to rethink the discourse on this issue by criticizing and elucidating the long-accepted assumption that religion is one of the main sources of interreligious tensions in Indonesia. This study chose a critical qualitative review to extract data and information from previous studies and reports regarding this issue. The results of this study cover such main elements as causes of interreligious conflicts, assumptions on religious conflicts, implications of religious conflicts on the future of Indonesian multicultural society, and a short-term outlook of interreligious conflicts in the country. This article concludes that Indonesia provides many unique contexts and aspects in comprehensively understanding interreligious tensions.